Immune Thrombocytopenia Induced by Immune Checkpoint Inhibitors in Solid Cancer: Case Report and Literature Review - Liu, Xiaolin; Liang, Xiuju; Liang, Jing; Li, Yan; Wang, Jun (Frontiers in Oncology, 2020)
Immune checkpoint inhibitors, including antibodies targeting programmed cell death protein-1 (PD-1) and its receptor programmed cell death ligand-1 (PD-L1), represent promising therapeutic strategies for advanced human malignancies. However, a subgroup of patients experiences various autoimmune toxicities, termed immune-related adverse events (irAEs), that occur as a result of on-target and off-tumor autoimmune responses. Although irAEs are generally confirmed to be less severe than toxicities caused by conventional chemotherapy and targeted therapy, uncommon irAEs, such as immune thrombocytopenia, may occur with a very low incidence and sometimes be severe or fatal. This review focuses on the epidemiology, clinical presentation, and prognosis of immune thrombocytopenia occurring in advanced cancer patients induced by immune checkpoint inhibitors, especially in those with PD-1 or PD-L1 inhibitor treatment. We also first present one patient with non-small cell lung cancer who received the PD-L1 inhibitor durvalumab and developed severe thrombocytopenia.